IMPLEMENTASI MODEL PEMBELAJARAN EXCELLENT DAN MEDIA AUGMENTED REALITY UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA (Adi Widya: Jurnal Pendidikan Dasar, 2023)
21st century education has a more complex task, not just imparting knowledge. Rather it touches on the skills needed by students including critical thinking skills and adaptation to the use of technology which must be integrated in learning. If this is not the case, students' thinking skills will be low and they will not have mastery of technology. The problem in this study is the low learning activity and high-level thinking skills of students in learning Mathematics. The reason is because learning is not student-centered and has not facilitated the development of higher-order thinking skills. This will have an impact on low student learning outcomes and ability in problem solving. Efforts to overcome these problems are by applying the EXCELLENT model and Augmented Reality media. This study aims to describe the improvement of the quality of learning through teacher activities, to analyze the improvement of students' critical thinking skills, and learning outcomes. This study used Classroom Action Research which was conducted in 4 meetings. The research subjects were 21 grade IV students. Aspects observed in this study include critical thinking skills, and student learning outcomes. So that the results of teacher activity at meeting I scored 36 criteria for balance, meeting II scored 43 criteria very well, meeting III scored 45 criteria very well, and meeting IV scored 48 criteria very well. Aspects of critical thinking skills at meeting I 71.43%, meeting II score 85.71, meeting III 90.48%, and meeting IV 100% with the criteria of all students being very skilled. And student learning outcomes at meeting I 61.90%, meeting II score 80.95%, meeting III 90.48%, and meeting IV 100% with the criteria of all students being very thorough.